HISTOPATHOLOGICAL LIVER TISSUES OF ALLOXAN-INDUCED WISTAR RATS THAT GIVEN LAWSONIA INERMIS (LINN.) LEAVES' ETHANOLIC EXTRACT - Sari, Mutiara Indah; Anggraini, Dwi Rita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of this research was to see the effect of Lawsonia inermis (Linn.) leaves ethanolic extract (LLEE) on liver histopathological of alloxan-induced Wistar rats. Methods: Thirty-five of male Wistar rats grouped into five groups, i.e., K (normal) given 0.9% NaCl solution and P1–P4 were induced using alloxan (120 mg/kg BW) intraperitoneally. P2–P4 was given LLEE, i.e., 200 mg/kg BW, 400 mg/kg BW, and 600 mg/kg BW for 28 days. On 29th day, all Wistar rats of the group were sacrificed to take its liver. Histology preparation of liver by paraffin slicing method of hematoxylin-eosin staining. The observation was done under a microscope with ×40 and ×100 magnification. Observation of the liver histopathological includes changes of the central venous, sinusoid, hepatocyte morphology, and glycogen accumulation, P1–P4 compared to K. Result: The results showed that in P4 group, LLEE dose 600 mg/Kg BW for 28 days able to improve liver tissues structure of alloxan-induced Wistar rats. Conclusion: The LLEE at dose 600 mg/Kg BW effective can restore the liver destruction of alloxan-induced Wistar rats.